2023
DOI: 10.3390/su151410968
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Methods for Woody Volume Prediction in Eucalyptus

Abstract: Machine learning (ML) algorithms can be used to predict wood volume in a faster and more accurate way, providing reliable answers in forest inventories. The objective of this work was to evaluate the performance of different ML techniques to predict the volume of eucalyptus wood, using diameter at breast height (DBH) and total height (Ht) as input variables, obtained by measuring DBH and Ht of 72 trees of six eucalyptus species (Eucalyptus camaldulensis, E. uroplylla, E. saligna, E. grandis, E. urograndis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…From this approach, all data points are predicted and validated, while still keeping a separate training set. This strategy has been widely adopted in ML analyses to avoiding overfitting or biased learning (Granholm et al, 2012;André et al, 2022;Ramos et al, 2020;Gava et al, 2022;Baio et al, 2023;Santana et al, 2023a;Santana et al, 2023b). Additionally, the cross-validation strategy provides the prediction results of one variable for each fold (k), making it possible to have repetitions for the model's accuracy values both in classification and regression studies, such as correlation between observed versus predicted (André et al, 2022;Baio et al, 2023;Santana et al, 2023b).…”
Section: Machine Learning Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…From this approach, all data points are predicted and validated, while still keeping a separate training set. This strategy has been widely adopted in ML analyses to avoiding overfitting or biased learning (Granholm et al, 2012;André et al, 2022;Ramos et al, 2020;Gava et al, 2022;Baio et al, 2023;Santana et al, 2023a;Santana et al, 2023b). Additionally, the cross-validation strategy provides the prediction results of one variable for each fold (k), making it possible to have repetitions for the model's accuracy values both in classification and regression studies, such as correlation between observed versus predicted (André et al, 2022;Baio et al, 2023;Santana et al, 2023b).…”
Section: Machine Learning Analysismentioning
confidence: 99%
“…This strategy has been widely adopted in ML analyses to avoiding overfitting or biased learning (Granholm et al, 2012;André et al, 2022;Ramos et al, 2020;Gava et al, 2022;Baio et al, 2023;Santana et al, 2023a;Santana et al, 2023b). Additionally, the cross-validation strategy provides the prediction results of one variable for each fold (k), making it possible to have repetitions for the model's accuracy values both in classification and regression studies, such as correlation between observed versus predicted (André et al, 2022;Baio et al, 2023;Santana et al, 2023b). This makes it possible to carry out statistical tests to compare or group means for the different techniques, to be described in detail in the next subtopic, which provides an accurate recommendation about the best ML models.…”
Section: Machine Learning Analysismentioning
confidence: 99%